The effect of text message reminders to health workers on quality of care for malaria, pneumonia, and diarrhea in Malawi: a cluster-randomized, controlled trial - Steinhardt, LC; Mathanga, DP; Mwandama, D; Nsona, H; Moyo, D; Gumbo, A; Kobayashi, M; Namuyinga, R; Shah, MP; Bauleni, A; Troell, P; Zurovac, D; et al. (American Society of Tropical Medicine and Hygiene, 2019)
The use of mobile technologies in medicine, or mHealth, holds promise to improve health worker (HW) performance, but evidence is mixed. We conducted a cluster-randomized controlled trial to evaluate the effect of text message reminders to HWs in outpatient health facilities (HFs) on quality of care for malaria, pneumonia, and diarrhea in Malawi. After a baseline HF survey (2,360 patients) in January 2015, 105 HFs were randomized to three arms: 1) text messages to HWs on malaria case management; 2) text messages to HWs on malaria, pneumonia, and diarrhea case management (latter two for children < 5 years); and 3) control arm (no messages). Messages were sent beginning April 2015 twice daily for 6 months, followed by an endline HF survey (2,536 patients) in November 2015. An intention-to-treat analysis with difference-in-differences binomial regression modeling was performed. The proportion of patients with uncomplicated malaria managed correctly increased from 42.8% to 59.6% in the control arm, from 43.7% to 55.8% in arm 1 (effect size −4.7%-points, 95% confidence interval (CI): −18.2, 8.9, P = 0.50) and from 30.2% to 50.9% in arm 2 (effect size 3.9%-points, 95% CI: −14.1, 22.0, P = 0.67). Prescription of first-line antibiotics to children < 5 years with clinically defined pneumonia increased in all arms, but decreased in arm 2 (effect size −4.1%-points, 95% CI: −42.0, 33.8, P = 0.83). Prescription of oral rehydration solution to children with diarrhea declined slightly in all arms. We found no significant improvements in malaria, pneumonia, or diarrhea treatment after HW reminders, illustrating the importance of rigorously testing new interventions before adoption.